2014
DOI: 10.3389/fmicb.2014.00191
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of plants by human pathogenic bacteria in the course of organic vegetable production

Abstract: In recent years, increasing numbers of outbreaks caused by the consumption of vegetables contaminated with human pathogenic bacteria were reported. The application of organic fertilizers during vegetable production is one of the possible reasons for contamination with those pathogens. In this study laboratory experiments in axenic and soil systems following common practices in organic farming were conducted to identify the minimal dose needed for bacterial colonization of plants and to identify possible factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The labeling was conducted in a 2 ml tube according to Hofmann et al (2014) with modifications (probes and hybridization conditions are listed in Table 1). To avoid loss of rhizosphere soil adhering to the root, the samples were treated very carefully and all steps were subsequently performed in the same tube without touching the sample with the tip of the pipette.…”
Section: Fluorescence-in Situ-hybridization (Fish) and Confocal Lasermentioning
confidence: 99%
“…The labeling was conducted in a 2 ml tube according to Hofmann et al (2014) with modifications (probes and hybridization conditions are listed in Table 1). To avoid loss of rhizosphere soil adhering to the root, the samples were treated very carefully and all steps were subsequently performed in the same tube without touching the sample with the tip of the pipette.…”
Section: Fluorescence-in Situ-hybridization (Fish) and Confocal Lasermentioning
confidence: 99%
“…Both animals and the environment in which agricultural plants are grown serve as reservoirs for these pathogens (Based on Barak and Schroeder, 2012). needed to improve food safety. For example, in the work of Hoffman et al (2014), studies were conducted to investigate the minimal number of Salmonella enterica sv. Weltevreden, Listeria monocytogenes EGD-E sv.…”
Section: Amylasementioning
confidence: 99%
“…Contamination of plants by human pathogens can occur at the farm level and a greater understanding of key contamination routes is needed to improve food safety. For example, in the work of Hoffman et al (), studies were conducted to investigate the minimal number of Salmonella enterica sv. Weltevreden, Listeria monocytogenes EGD‐E sv.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also clear that the ability of opportunistic human pathogens (such as non-typhoidal strains of Salmonella enterica) to persist outside of their animal hosts, and to colonize and multiply within plants, is an important factor leading to the outbreaks of human salmonellosis from the consumption of fruits and vegetables Martinez-Vaz et al, 2014). Salmonella can persist in manure-amended soils for over 7 months, and the pathogen can be detected on aboveground parts of leafy greens and root vegetables grown in these amended soils for 2-3 months (Islam et al, 2004;Hofmann et al, 2014). These field reports are consistent with laboratory studies that demonstrated that plant-associated Salmonella and pathogenic E. coli ingested by vertebrate and invertebrate herbivores were shed by the animals in their feces and were capable of re-colonizing plants once excreted into the environment (Semenov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%